The Morality Factors in Preventing Fraud in Village Fund Management - Fatchur Rochman; Nurharibnu Wibisono; Herry Purnomo; Arini Wildaniyati; Pramita Mawar Dianti (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study seeks to examine the role of morality as a mediating variable in the association among the internal control system (SPI) and the village officials competence (KAD) on efforts to avoid fraud in the management of Village Funds in Ngariboyo District, Magetan Regency. Background Problem: Following the application of Law No. 6 of 2014 on Villages, the allocation of Village Funds has increased substantially each year. This situation places greater responsibility on Village Governments to ensure that fraudulent practices in Village Fund management are effectively prevented. Novelty: The research offers a new perspective by emphasizing the significance of morality (MOR) as a mediator among SPI and village officials’ competence (KAD) in influencing fraud prevention (FRA) within the Village Fund management process. Research Methods: A quantitative research design was employed. The sample was selected through purposive sampling, involving 10 villages in Ngariboyo District, Magetan Regency. A total of 50 respondents who were directly engaged in the Village Funds management participated in the research. Path analysis was conducted using the SmartPLS 4 software. Findings/Results: The findings reveal that SPI, the competence, and morality individually exerts a significant positive effect on preventing fraud. Morality does not mediate the relationship among SPI and fraud avoidance, but it does mediate the influence of village officials’ competence on fraud prevention. Conclusion: Strengthening the implementation of SPI, enhancing the competence, and fostering strong moral values are crucial for preventing fraud in management of Village Fund. Enhancing the ethical standards of village officials is anticipated to contribute to limiting corruption and minimizing fraudulent use of Village Funds.